The Ex Hoc Infrastructure Framework: Enhancing Traffic Safety through LIfe Warning Systems - Hansen, Klaus Marius; Kristensen, Lars M.; Eskildsen, Toke; Nielsen, Kenneth-Daniel; Thorup, Rolf E.; Fridthjof, Jack; Merrild, Ulrik; Eskildsen, Jørn (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
New pervasive computing technologies for sensing and communication open up novel possibilities for enhancing traffic safety. We are currently designing and implementing the Ex Hoc infrastructure framework for communication among mobile and stationary units including vehicles. The infrastructure will connect sensing devices on vehicles with sensing devices on other vehicles and with stationary communication units placed alongside roads. The current application of Ex Hoc is to enable the collection and dissemination of information on road condition through LIfe Warning Systems (LIWAS) units.